2020
DOI: 10.1097/mca.0000000000000818
|View full text |Cite
|
Sign up to set email alerts
|

Association of lymphocyte-to-monocyte ratio with the long-term outcome after hospital discharge in patients with ST-elevation myocardial infarction: a retrospective cohort study

Abstract: Objective Lymphocyte-to-monocyte ratio (LMR), a novel systemic inflammatory factor, correlates with adverse outcomes in patients with cardiovascular disease. However, data are limited regarding the prognostic value of LMR in patients with ST-elevation myocardial infarction (STEMI) after hospital discharge. Therefore, the aim of our study was to evaluate the prognostic impact of admission LMR in hospital survivors of STEMI. Methods This retrospective obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 35 publications
1
23
0
1
Order By: Relevance
“…In this meta-analysis, we enrolled 5 studies comprising 4343 patients to investigate the prognostic value of the LMR in patients with ACS [18,[21][22][23][24]. The present study showed that LMR might be a predictor for short-term mortality/MACE.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…In this meta-analysis, we enrolled 5 studies comprising 4343 patients to investigate the prognostic value of the LMR in patients with ACS [18,[21][22][23][24]. The present study showed that LMR might be a predictor for short-term mortality/MACE.…”
Section: Discussionmentioning
confidence: 70%
“…The result showed that LMR predicted short-term mortality/MACE (HR = 3.44, 95% CI: 1.46-8.14, P < 0.05, Figure 2A), with low levels of heterogeneity among studies (I 2 = 0%). The combined analysis of 5 studies covering 4343 patients described the relationship between LMR and longterm mortality/MACE [18,[21][22][23][24]. The pooled outcome for low LMR value compared with high LMR value group was found to be 1.70 (95% CI: 1.36-2.13, P < 0.05, Figure 2B), with moderate levels of heterogeneity among studies (I 2 = 46.8%).…”
Section: Lmr and Mortality/macementioning
confidence: 95%
“…These studies were all observation researchers and one conducted in Netherlands [18], one conducted in Turkey [21], three conducted in China [22][23][24]. The mean age of the patients ranges from 60.77 to 65.12 years old.…”
Section: Resultsmentioning
confidence: 99%
“…The mean age of the patients ranges from 60.77 to 65.12 years old. Two studies in this meta-analysis enrolled STEMI patients [21,24], two studies enrolled NSTEMI patients [22,23], and the remaining one study enrolled ACS patients [18]. Two of studies explicitly stated that the patients underwent PCI [21,22], while others did not specify if enrolled patients underwent PCI [18,23,24].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation